Insubordinação E Desgarramento Nos Folhetins Do Jornal Do Comércio No Século XIX (PERcursos Linguísticos, 2022)
In this paper, we analyze the occurrence of independent clauses, taking, as our corpus, the newspaper serials published in Jornal do Commercio do Rio de Janeiro during the XIX century (AFFONSO JUNIOR, 2022). In this inquiry, we identified and described these clauses according to the phenomenon's categorization either as unattached clauses (DECAT, 2021; RODRIGUES, 2021) or as insubordinate ones (EVANS, 2007; EVANS & WATANABE, 2016; RODRIGUES, 2021), concerning the Functionalist theoretical framework. We aim to present, at first, a short bibliografic review comparing the traditional view and the Functionalist approach to the analysis of composed clauses. Therefore, still amid the Functionalist context, we went through independent clauses’ data to divide them between unattached and insubordinate ones so that we could check the possibilities of formal structures and semantic nuances. Concerning the results, 78 independent clauses were collected from 38 daily newspapers: 46 of them were unattached clauses and 32 were insubordinate ones. Some criteria, like the clause introducer, the punctuation and the verb tense, were considered. Concerning the semantic nuances, relations of cause, condition, consequence, exclamation and evaluation were noted. We believe that both unattached and insubordinate clauses were used in the Brazilian Portuguese back in the newspaper serials time.